2013
DOI: 10.1136/bjsports-2012-091837
|View full text |Cite
|
Sign up to set email alerts
|

Running in a minimalist and lightweight shoe is not the same as running barefoot: a biomechanical study

Abstract: Aim The purpose of this study was to determine the changes in running mechanics that occur when highly trained runners run barefoot and in a minimalist shoe, and specifically if running in a minimalist shoe replicates barefoot running. Methods Ground reaction force data and kinematics were collected from 22 highly trained runners during overground running while barefoot and in three shod conditions (minimalist shoe, racing flat and the athlete's regular shoe). Three-dimensional net joint moments and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
181
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(209 citation statements)
references
References 24 publications
22
181
5
Order By: Relevance
“…Specifically, our findings on Nike Free model agree with Willis and Davis (2014) who concluded that running in this shoe failed to result in changes in spatio-temporal parameters when compared with running in a standard running shoe. The results also agree with Bonacci et al (2013) and Sinclair et al (2013), who concluded that the mechanics of this footwear does not appear to closely mimic the kinematics of barefoot locomotion in experienced runners. In addition, our findings on the Vibram FiveFingers shoe confirm, even for rearfoot strikers, the findings of Squadrone and Gallozzi (2009), which found that this type of shoes have no significant effect on barefoot running kinematics.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Specifically, our findings on Nike Free model agree with Willis and Davis (2014) who concluded that running in this shoe failed to result in changes in spatio-temporal parameters when compared with running in a standard running shoe. The results also agree with Bonacci et al (2013) and Sinclair et al (2013), who concluded that the mechanics of this footwear does not appear to closely mimic the kinematics of barefoot locomotion in experienced runners. In addition, our findings on the Vibram FiveFingers shoe confirm, even for rearfoot strikers, the findings of Squadrone and Gallozzi (2009), which found that this type of shoes have no significant effect on barefoot running kinematics.…”
Section: Discussionsupporting
confidence: 81%
“…Runners seemed to progress towards a more midfoot strike while barefoot running, and this was confirmed by the foot contact angle, which was~40% less dorsiflexed in barefoot than in cushioned shoe. Similar adjustments have been reported by previous studies (Bonacci et al, 2013 , 2000;Hamill et al, 2011;Horvais & Samozino, 2013;Lieberman et al, 2010;Squadrone & Gallozzi, 2009) and are not particularly surprising. In a recent study, Paquette et al (2013) found that the strike index was greater in barefoot condition and in Vibram FiveFingers than in cushioned shoes, in both rearfoot and midfoot striker runners.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…There are different shoes in the market such as instable shoes; 5-toed shoes and the shoes designed for different sports such as running [8][9][10]. The purpose of using instable shoes is involving the muscles more, and as a result, strengthening the muscles and preventing their weaknesses in long-term that play an important role in kinematic and kinetic changes [11,12].…”
Section: Introductionmentioning
confidence: 99%